High Performance Multistring Converter Topology for Three-Phase Grid Tied 200 kW Photovoltaic Generating System - Mohammad Rustam M. L.; F. Danang Wijaya (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2017)
Under various external conditions, grid connected PV system performance is strongly affected by the topology that is used to connect a PV system with grid. This research aims to design a multistring based converter topology for three-phase grid connected 200 kW PV system that has a high performance in various operating conditions. Research was done by a simulation method using Matlab-Simulink with performance being evaluated including the generated power, efficiency, power quality in accordance with grid requirements, as well as the power flow. In the simulation, multistring converter topology was designed using two dc-dc boost multistring converters connected in parallel to a centralized of three-phase three-level NPC inverter with the size of the string being shorter and more parallel strings as well as the maximum voltage of the PV array of 273.5 V close to dc voltage reference of 500 V. Each dc-dc boost multistring converter have individual MPPT controllers. The simulation results showed that this multistring converter topology had a high performance in various operating conditions. This due to more power generated by the NPC inverter (> 190 kW) at the time of high power generation on the STC conditions (1000 W/m2, 25 oC), the lowest efficiency of the total system is 95.08 % and the highest efficiency of the total system is 99.4 %, the quality of the power generated in accordance with the requirements of grid, as well as the inverter put more active power to the grid and less reactive power to the grid. The response of the inverter slightly worse for loads with greater reactive power and unbalanced.